2021
DOI: 10.1111/codi.15541
|View full text |Cite
|
Sign up to set email alerts
|

Urinary dysfunction after colorectal cancer treatment and its impact on quality of life – a national cross‐sectional study in women

Abstract: Aim The aim of this study was to investigate urinary dysfunction and its impact on the quality of life of colorectal cancer survivors. We also wanted to identify the risk factors for impaired urinary function. Method A national cross‐sectional study was performed including patients treated for colorectal cancer between 2001 and 2014. Patients answered questionnaires regarding urinary function and quality of life, including the International Consultation on Incontinence Questionnaire – Female Lower Urinary Trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The study was conducted as a national cross-sectional questionnaire women has been addressed in a separate article [14].…”
Section: Design and Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was conducted as a national cross-sectional questionnaire women has been addressed in a separate article [14].…”
Section: Design and Patient Selectionmentioning
confidence: 99%
“…Furthermore, we aimed to identify possible risk factors for the development of urinary dysfunction. Urinary function in women in the same population is described in a separate article [14].…”
mentioning
confidence: 99%
“…The mechanism of injury leading to urinary dysfunction is thought to be secondary to nerve damage during surgical resection of rectal tumors [53]. Studies have suggested worse urinary function in patients undergoing APR compared to those undergoing LAR; however, when controlled for other risk factors, these were not statistically significant [52,54,55]. The research on the impact of radiation on urinary dysfunction in rectal cancer survivors is mixed [51,54,56].…”
Section: Urinary Dysfunctionmentioning
confidence: 99%
“…Studies have suggested worse urinary function in patients undergoing APR compared to those undergoing LAR; however, when controlled for other risk factors, these were not statistically significant [52,54,55]. The research on the impact of radiation on urinary dysfunction in rectal cancer survivors is mixed [51,54,56]. Menopausal changes associated with chemotherapy and radiation can also lead to urinary dysfunction in women [57,58].…”
Section: Urinary Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation